Sistem Monitoring Indeks Standar Pencemaran Udara (ISPU) pada Wilayah Kota berbasis Internet of Things - Asrul, Asrul; Amir, Ashadi; Ilham, Muh (Universitas Muhammadiyah Jakarta, 2024)
The increase in the number of motorized vehicles in urban areas poses problems with air quality. Changes in air quality caused by harmful gases cannot be observed directly. In this study, an Internet of Things (IoT)-based air quality monitoring system was designed. The designed system consists of a sensor device that can measure CO, O3 and PM10 parameters integrated with a Microcontroller device. Prototype testing was carried out in Parepare City to observe the values of air quality parameters and ISPU through IoT-based applications for one week. The test results show that the highest air pollution level on the Pinrang-Parepare Axis Road occurs on Wednesdays, Thursdays and Sundays with the highest average ISPU being 500 and on Jalan Jendral Ahmad Yani the highest air pollution levels occur on Mondays, Saturdays and Sundays with the highest average ISPU being 300. The increase in ISPU values is affected by air temperature and humidity. The highest concentration occurs when the air temperature is low and the air humidity is high.